Endoscopic internal drainage with double pigtail stents for upper gastrointestinal anastomotic leaks: suitable for all cases? - Bin Chet Toh; Jingli Chong; Baldwin PM Yeung; Chin Hong Lim; Eugene KW Lim; Weng Hoong Chan; Jeremy TH Tan (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Surgeons and endoscopists have started to use endoscopically inserted double pigtail stents (DPTs) in the management of upper gastrointestinal (UGI) leaks, including UGI anastomotic leaks. We investigated our own experiences in this patient population. Methods From March 2017 to June 2020, 12 patients had endoscopic internal drainage of a radiologically proven anastomotic leak after UGI surgery in two tertiary UGI centers. The primary outcome measure was the time to removal of the DPTs after anastomotic healing. The secondary outcome measure was early oral feeding after DPT insertion. Results Eight of the 12 patients (67%) required only one DPT, whereas four (33%) required two DPTs. The median duration of drainage was 42 days. Two patients required surgery due to inadequate control of sepsis. Of the remaining 10 patients, nine did not require a change in DPT before anastomotic healing. Nine patients were allowed oral fluids within the 1st week and a soft diet in the 2nd week. One patient was allowed clear oral feeds on the 8th day after DPT insertion. Conclusions Endoscopic internal drainage is becoming an established minimally invasive technique for controlling anastomotic leak after UGI surgery. It allows for early oral nutritional feeding and minimizes discomfort from conventional external drainage.